Hamman's syndrome: a rare benign syndrome - Abdul Rahim, Aida; Yahaya, Mohd Taufiq; Mohd Shafie, Siti Nor Farhana; Ahmad Apandi, Laila Mastura (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Hamman’s syndrome by definition is spontaneous pneumomediastinum with the exclusion of thoracic trauma or iatrogenic cause. It is rare and is more common in adolescence male. Amongst the risk factors are underlying lung condition such as asthma and interstitial lung disease, drug inhalation and parturient woman. Patient usually presents with sudden onset of shortness of breath and chest pain with subcutaneous emphysema on examination. The diagnosis is confirmed with chest radiograph. The prognosis of Hamman’s syndrome is excellent. Most cases are self-limiting and resolve spontaneously. However, Hamman’s syndrome is a poorly recognised disease due to its rarity. Therefore, the patient may be subjected to misdiagnosis and treatment. This is a case report of Hamman’s syndrome misdiagnosed and treated as pneumothorax. The objective of this case report is to highlight the importance of differentiating this benign syndrome with life threatening differentials which may have similar clinical presentation. Thus, avoiding unnecessary costly investigation, treatment and invasive procedures.